Bidirectionality in synesthesia: evidence from a multiplication verification task. - Gevers, W; Imbo, I; Cohen Kadosh, R; Fias, W; Hartsuiker, R (2010)
Color-grapheme synesthetes automatically perceive achromatic numbers as colored (e.g., 7 is turquoise). Up until recently, synesthesia was believed to be unidirectional. For instance, the number 7 gives rise to the percept of turquoise but the perception of turquoise does not trigger the number 7. However, some recent studies argue for bidirectional connections Cohen Kadosh et al., 2005; Johnson et al., 2007; Knoch et al., 2005). In this study, a multiplication verification task (e.g., 7 x 2 = 14, true/false?) was used to test bidirectionality. In agreement with previous studies we observed that the presentation of colors evokes numerical magnitudes. The current findings add two important notions to previous studies: (a) The influence of color on the processing of numerical information can be extended to multiplication verification tasks and (b) The perception of color can both facilitate and interfere with the processing of digit-related information.